A Spontaneous Mutation in Taar1 Impacts Methamphetamine-Related Traits Exclusively in DBA/2 Mice from a Single Vendor - Reed, Cheryl; Baba, Harue; Zhu, Zhen; Erk, Jason; Mootz, John R.; Varra, Nicholas M.; Williams, Robert W.; Phillips, Tamara J. (Frontiers in Pharmacology, 2018)
Major gene effects on traits associated with substance use disorders are rare. Previous findings in methamphetamine drinking (MADR) lines of mice, bred for high or low voluntary MA intake, and in null mutants demonstrate a major impact of the trace amine-associated receptor 1 (Taar1) gene on a triad of MA-related traits: MA consumption, MA-induced conditioned taste aversion and MA-induced hypothermia. While inbred strains are fundamentally genetically stable, rare spontaneous mutations can become fixed and result in new or aberrant phenotypes. A single nucleotide polymorphism in Taar1 that encodes a missense proline to threonine mutation in the second transmembrane domain (Taar1m1J) has been identified in the DBA/2J strain. MA is an agonist at this receptor, but the receptor produced by Taar1m1J does not respond to MA or endogenous ligands. In the present study, we used progeny of the C57BL/6J x DBA/2J F2 cross, the MADR lines, C57BL/6J x DBA/2J recombinant inbred strains, and DBA/2 mice sourced from four vendors to further examine Taar1-MA phenotype relations and to define the chronology of the fixation of the Taar1m1J mutation. Mice homozygous for Taar1m1J were found at high frequency early in selection for high MA intake in multiple replicates of the high MADR line, whereas Taar1m1J homozygotes were absent in the low MADR line. The homozygous Taar1m1J genotype is causally linked to increased MA intake, reduced MA-induced conditioned taste aversion, and reduced MA-induced hypothermia across models. Genotype-phenotype correlations range from 0.68 to 0.96. This Taar1 polymorphism exists in DBA/2J mice sourced directly from The Jackson Laboratory, but not DBA/2 mice sourced from Charles River (DBA/2NCrl), Envigo (formerly Harlan Sprague Dawley; DBA/2NHsd) or Taconic (DBA/2NTac). By genotyping archived samples from The Jackson Laboratory, we have determined that this mutation arose in 2001 – 2003. Our data strengthen the conclusion that the mutant Taar1m1J allele, which codes for a non-functional receptor protein, increases risk for multiple MA-related traits, including MA intake, in homozygous Taar1m1J individuals.